Reconstruction of Acetabular Wall Using Autologous Bone Graft Following Resection of Pelvic Chondrosarcoma: Surgical Technique and Functional Outcome - Rendy Cahya Soetanto; Muhammad Naseh Budi; Darmadji Ismono (National Cancer Center - Dharmais Cancer Hospital, 2019)
Background: Pelvic chondrosarcoma may be difficult to manage due to its proximities with vital structures. The study aimed to explain an alternative surgical technique for acetabular reconstruction.Case Presentation: We present a case of a 48-year-old female with large chondrosarcoma of the superior and inferior pubic rami with medial acetabular wall involvement. Pelvic type 3 resection was performed. There was a defect at medial acetabulum after resection. The defect was covered by autograft from iliac and fixation using screws. Rotational pelvic stability was maintained using a reconstruction plate. The functional outcome was assessed 6 months after operation using MSTS and the score was 30, which was painless, full weight bearing, normal gait, and no pain. Conclusions: Reconstruction of the pelvis after tumor resection requires a careful preoperative patient evaluation and extensive bone and soft tissue resection to achieve negative tumor margins and stable reconstruction of the osseous and soft tissue defects.